In Search of Success : Case Studies in Justice Sector Development in Sub-Saharan Africa - Walsh, Barry (World Bank, 2012)
The World Bank, Department for International Development (DFID) and other donors have long been engaged in legal and judicial reform in sub-Saharan Africa in such areas as legal drafting, strengthening court administration, judicial training, and the empowerment of citizens through a better understanding of the legal system. This has often been done on an ad hoc basis with only limited review of other reform efforts in the region. In order to foster a more responsive approach to justice sector development programs, a collection of case studies was commissioned. One of the more daunting tasks was identifying notable justice sector developments or reforms, which offered specific impacts and which could be examined through both a desk review and field research. Independent of the funding source, the evidence base was not only limited but revealed a need for donors themselves to invest in better data collection, which could then be analyzed and measured against benchmarks or objectives such as improved access to justice. There is a significant need to review and learn from experiences, including controversial ones, in Africa's justice sectors. These case studies are not homogenous largely because their subjects vary and span a wide array of developments that reflect the realities of the region. Each story stands alone and is in no particular order. In the final chapter, the conclusions offered in each story are digested into ideas for future actions. The collection also represents a modest range of stories and it is to be hoped that other cases will be identified and shared. A comparison of experiences of sector-wide programs (SWAPs), for example, could help both donors and governments enhance socio-economic impact. It should be noted that the emphasis in this report is on providing information about positive directions in justice sector development and the ways in which lessons learned might be applied to achieve greater impact in the future. The anticipated value of this collection is that some of the conclusions or actions may be taken up and used to contribute to improvements by those committed to improving the rule of law in sub-Saharan Africa and is in search of 'success'.